A comparison of standard C-reactive protein laboratory measurement to point of care C-reactive protein test in a neonatal intensive care unit setting - Prince, Kim Didi (Department of Paediatrics and Child Health, 2017)
Background: Laboratory biomarkers are important adjuncts to clinical data in diagnosing neonatal sepsis. Available diagnostic tests often provide results 6 to 48 hours later. A bedside C-reactive protein (CRP) test may be able to exclude or diagnose sepsis within minutes. Objectives: The objectives were to validate the Alere AfinionTM point of care test (POCT) CRP in a tertiary neonatal unit against the gold standard CRP assay in use by the National Health Laboratory service and to determine the difference in time to obtaining a result between the two systems. Methods: A prospective observational study was conducted between February 2015 and June 2015. Neonates who were clinically indicated to undergo CRP testing were simultaneously tested using the POCT and laboratory assays. The sensitivities, specificities and predictive values for the POCT, with the laboratory test as the reference test were determined. The time to results between the two tests was compared. Results: There were 139 measured CRP sample pairs from patients with suspected or proven neonatal sepsis. Using 10 mg/L as the cutoff value for both CRP tests, the sensitivity, specificity, positive predictive value and negative predictive value were 97.4%, 99%, 97.4% and 99% respectively. The area under the receiver operating characteristic curve was 0.99 (p<0.001). The time to point of care result was 4 minutes. Laboratory results were registered at a mean of 4.7 hours but only checked after a mean of 6.8 hours. Conclusions: The POCT CRP and laboratory CRP test have excellent correlation in neonates and may be a useful, quick, reliable method to rationalise antibiotic usage, reduce costs and allow for earlier patient discharge.